Molecular markers for sex identification in papaya - Oliveira, Eder Jorge de; Dantas, Jorge Luiz Loyola; Castellen, Milene da Silva; Lima, Diego Souza de; Barbosa, Helder de Souza; Motta, Tiago Borges Nunes (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was the validation of previous discovered sex related molecular markers of papaya, aiming at the indirect selection of Brazilian commercial genotypes. Two varieties of the Solo group and two hybrids of the Formosa group (20 plants for genotype), four SCAR (Sequence Characterized Amplified Region) and one RAPD (Random Amplified Polymorphic DNA) markers were used. All hermaphrodite and female plants were correctly predicted by RAPD BC210, showing its high potential for marker assisted selection in important commercial genotypes used in Brazil. The SCAR markers did not show the true sex identification of these genotypes, revealing the presence of false positives and negatives in the analyses.